Molecular Evaluation of Genomic Stability of Banana Plants Developed by in Vitro Clonal Propagation - Asha S. Nayar (Department of Horticulture, College of Agriculture, 2001)
Attempts were made for evaluating the genomic stability of in vitro propagated Peel banana plantlets at molecular level, during 1999- 2000, at the Plant Molecular Biology and Biotechnology Centre, College of Agriculture, Vellayani. Efforts were made to standardise the DNA isolation method and PCR amplification conditions, to identify the primer producing reproducible polymorphic bands and to compare the banding patterns characteristic to the subcultures and the mother plant. The emerging leaves of the Rxl banana plants before they fully unfurl, gave the highest DNA yield of2825 ng! III whereas, the in vitro leaves gave the highest optical density (OD) ratio of 1.76. The purity of DNA was the highest (0. D. ratio 1.81) while CTAB method (Scott et al., 1994) was adopted. The DNA quantity was the highest in the Walbot's method, viz. 3000 ng! Ill. The OD ratio increased from 1.33 to 1.46 on addition of proteinase k. Additional purification step increased the OD ratio from 0.93 to 1.18. One per cent polyvinyl pyrrolidone (PVP) and 1.5 per cent J3-mercaptoethanol, when added in the extraction buffer produced transparent DNA pellet. 0.9 per cent and 1.4 per cent of agarose concentration were found to be the best for the genomic DNA and RAPD banding patterns respectively. The optimum PCR programme W<!§"an initial denaturation at 95° C for 3.0 minutes, followed by 45 cycles of denaturation at 95° C for 1.0 minute, annealing at 36° C for 1.0 minute and 30 seconds, and extension at 72° C for 2.0 minutes. The synthesis step was extended further by 6.0 minutes. A total of 134 RAPDs were generated when PCR amplification was done of which 130 were polymorphic. OPA- 06, OPB-IO and